Morphometric analysis of diameter and relationship of vertebral artery with respect to transverse foramen in Indian population - Binit Sureka; Mahesh Kumar Mittal; Aliza Mittal; Mukul Sinha Kanhaiya Agarwal; Narendra Kumar Bhambri; Brij Bhushan Thukral (Indian Journal of Radiology and Imaging, 2015)
Purpose: To study the location, origin, size and relationship of the vertebral artery and the transverse foramina in the lower cervical spine by computed tomographic angiography (CTA) measurements in the Indian population. Materials and Methods: A retrospective review of multi-detector CT (MDCT) cerebral angiography scans was done between June 2011 and February 2014. A total of 120 patients were evaluated. The diameter of the vertebral artery (AL) and the shortest distance between the vertebral artery and the medial (M), lateral (L), anterior (A), and posterior (P) borders of transverse foramen were studied. In addition, the shortest distance between the vertebral artery and pedicle (h) was also analyzed. Statistical Analysis: The means and their standard deviations (SD) were calculated in both the sexes. The t-tests were performed to look for significant sexual difference. Results: The largest vertebral artery diameter (AL) was at level C7 on the right side (3.5 ± 0.8) and at the level of C5 on the left side (3.7 ± 0.4). Statistically significant difference between males and females were seen at levels C4, C5, and C7. The diameter of the vertebral artery was smaller in females than males. The L value was greater than other parameters (M, A, P) at the same level in all the measurements. The h value was greatest at C6 level and shortest at C5. Conclusion: CTA is necessary before pedicle screw fixation due to variation in measurements at all levels. The highest potential risk of vertebral artery injury during cervical pedicle screw implantation may be at C5, then at C4, and the safest is at C7.